Prognostic analysis of stage IIIC1p cervical cancer patients - Gao, Ting; Yang, Zixuan; Wei, Liqun; Tang, Xiaobi; Ma, Shanshan; Jiang, Li; Zhang, Yong; Wu, Fang (Frontiers in Oncology, 2024)
Background: Stage IIIC1p cervical cancer is characterized by marked heterogeneity and considerable variability in the postoperative prognosis. This study aimed to identify the clinical and pathological characteristics affecting the survival of patients diagnosed with stage IIIC1p cervical cancer. Methods: We retrospectively analyzed patients diagnosed with stage IIIC1p cervical cancer who underwent radical hysterectomy and lymph node dissection between March 2012 and March 2022. Overall survival (OS) was estimated using Kaplan-Meier survival curves. Univariate and multivariate Cox proportional hazards models were used to evaluate prognostic factors for OS and forest plots were used to visualize these findings. Nomogram charts were created to forecast survival rates at 3 and 5 years, and the accuracy of predictions was evaluated using Harrell's concordance index (C-index) and calibration curves.Results: The study cohort comprised 186 women diagnosed with stage IIIC1p cervical cancer. The median follow-up duration was 51.1 months (range, 30-91 months), and the estimated 5-year OS rate was 71.5%. Multivariate analysis revealed that concurrent chemoradiotherapy plus adjuvant chemotherapy (CCRT + AC), monocytelymphocyte ratio (MLR), ratio of lymph node metastasis (LNM), and squamous cell carcinoma antigen (SCCA) levels independently predicted OS.Conclusions: Significant prognostic disparities exist among patients diagnosed with stage IIIC1p cervical cancer. MLR, ratio of LNM, and SCCA were associated with poor OS. In contrast, the CCRT + AC treatment regimen appeared to confer a survival advantage.